Protective systems for high temperature applications : from theory to industrial implementation - Schütze, Michael (Maney Pub., 2011)
Annotation Recent initiatives and developments in high temperature technology aim at the exploitation of fuels end processes at the edge of present materials capabilities, driving service temperatures higher and operating within ever more aggressive environmental conditions. The major driving force behind this trend is increased efficiencies and further growing efforts in environmental protection. The key to reliable operation of components for sufficiently long service periods to a large extent lies in the high temperature properties of the materials used, with high temperature corrosion resistance as the major life and performance-limiting factor. As conventional alloy design invariably leads to a compromise between mechanical strength and corrosion resistance industry has turned to coatings to provide improved materials performance. Consequently there is extensive worldwide activity to develop high performance protective coating systems, to prevent or minimise damage by corrosion, as well as by abrasion, wear and erosion at elevated temperature. Many of these systems (which may consist of surface modified bulk materials or genuine coating systems and in some cases also of special alloy approaches) are based on systematic development starting from present theoretical understanding including laboratory data and ending up in tailor-made solutions for industrial applications.
"Published for the European Federation of Corrosion by Maney Publishing on behalf of The Institute of Materials, Minerals & Mining."
"Selected proceedings of an EFC Workshop held in Frankfurt on 12-13 October 2006"--Page 4 of cover.
Keywords: Materials at high temperatures -- Protection -- Congresses.; Materials at high temperatures -- Corrosion -- Congresses.; elektronické knihy; electronic books